Traditional Sporting Games as an emotional induction procedure - Moya-Higueras, Jorge; March-Llanes, Jaume; Prat, Queralt; Muñoz-Arroyave, Verónica; Lavega-Burgués, Pere (Frontiers in Psychology, 2023)
Experimental designs to induct emotional states have used still procedures frequently. However, more naturalistic methods should imply letting participants move and interact freely among other participants. Traditional Sporting Games (TSG) have the abovementioned characteristics. We developed three studies, with three different TSG (Sitting Ball Game, Four Corner Game, and Pitchers Game). The general aim of this work was showing whether the different roles which allowed executing ambivalent interactions, induced different emotional states in college students. Before beginning playing, all the samples answered the Positive and Negative Affect Schedule (PANAS) in a mood version. After playing, participants had to report retrospectively the emotional state they were feeling in each role of the game responding to the Self-Assessment Manikin, PANAS, and Games and Emotion Scale-II. Statistical analyses were performed by ANOVA procedures, calculating corresponding effect sizes. Consistently, but specifically to each game, still roles inducted less positive and more negative emotions. Regarding the active ones, when the role allowed catching other players, more positive and less negative emotions were found. On the contrary, when developing one active role that implied an increased likelihood to be caught, more negative and less positive emotions were experienced. We found some significant interactions between mood before playing and the role played. To conclude, TSG could be an adequate procedure to induct emotional states and to study emotional conditions from a naturalistic way, showing ecological validity.